What Do University Students Know About SDG4 Quality Education? A Case Study of Business Management Education at Telkom University Indonesia - Ratna Lindawati Lubis; Audry Pusparani (Jurnal Manajemen Indonesia, 2022)
Sustainable Development Goals are the global action plans constituted by world leaders including Indonesia at the 70th general assembly of the United Nations in New York. The next global action known as SDGs has formed 17 objectives with 169 targeted action plans up until 2030 with the theme “Transforming our world: The 2030 agenda for Sustainable Development Goals”. As a form of participation in this action, Indonesian Government has officially issued a Presidential Regulation of Republic Indonesia Number 59 of 2017 concerning the Implementation in Achieving the Sustainable Development Goals. This research has the aim to determine the quality of education as one of the purposes in SDGs, namely SDG 4 in the Communication and Informatics Business Management (MBTI) study program based on the perceptions of the students taking entrepreneurship course. By gauging the level of understanding (cognitive), the ability to advocate (socio-emotional), the participation (behavioral) of the students related to SDG 4, also to measure the conformity of MBTI study program’s vision and mission with 3 Pillars of the Tridharma where it is linked directly to SDG 4 targets. As well as to disclose the readiness of MBTI study program in actualizing SDG 4 targets based on the perspective of students taking entrepreneurship courses. In order to identify each category for every variable, the writer is using descriptive analysis. The result shows that the cognitive, socio-emotional, and behavioral aspects of MBTI students are well mannered. The same thing applies to the conformity of its vision and mission linked with 3 Pillars of the Tridharma also the readiness of the study program.